An Empirical Analysis of Capital Structure Determinants: Evidence from The Indian Corporate Sector (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Existing empirical research on the determinants of capital structure has been largely restricted to the advanced countries like United States, Japan, France, U. K., Germany etc. The present paper makes an empirical attempt to study the determinants of capital structure of developing countries through a case of the Indian corporate sector by using a panel data approach. The present study, although an exploratory effort, is limited to 298 out of top 500 manufacturing firms selected on the basis of the turnover for the year 2004-2005 which covers the time span of eleven years commencing from 1995-96 to 2005-06. The results of the study demonstrate that that uniqueness and liquidity are the important determinants of capital structure of the Indian corporate sector during the period under study. It is also found that earning rate, cash flow coverage ratio, size (total assets), growth of assets, non-debt tax shield, dividend payout ratio and operating leverage are having a little influence on the capital structure of the Indian corporate sector during the period under study.